(untitled) (The Pakistan Development Review, 1994)
With the abolition of Mirdom in 1972, social and economic change picked up in the Northern Areas of Pakistan. Apart from the government, the other significant agent of change has been the Aga Khan Rural Support Programme (AKRSP). For any such programme to be successful it is important that the programme is designed, implemented and managed, keeping in view the local socio-economic conditions, ecology and, most importantly, characteristics of the poor. This paper is based on a study conducted in two villages, Rabat and Chaprote, in the Nagar Sub-division of Gilgit District, in 1990-91.1 It seeks to examine the projects launched by the AKRSP, the relevance of these projects to the local context, and their performance at the micro-level.